2010
DOI: 10.1074/jbc.m110.137802
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Palmitoyltransferases Are Required for Palmitoylation-dependent Regulation of Large Conductance Calcium- and Voltage-activated Potassium Channels

Abstract: Palmitoylation is emerging as an important and dynamic regulator of ion channel function; however, the specificity with which the large family of acyl palmitoyltransferases (zinc finger Asp-His-His-Cys type-containing acyl palmitoyltransferase (DHHCs)) control channel palmitoylation is poorly understood. We have previously demonstrated that the alternatively spliced stress-regulated exon (STREX) variant of the intracellular C-terminal domain of the large conductance calcium- and voltage-activated potassium (BK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 34 publications
1
87
0
Order By: Relevance
“…16,[23][24][25] We show that endogenous DHHC7 constitutively co-immunoprecipitates with endogenous Fas in SW480 LacZ cell lysate ( Figure 2e). As expected, this DHHC7/Fas association is enhanced when Fas WT is overexpressed (Figure 2e).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…16,[23][24][25] We show that endogenous DHHC7 constitutively co-immunoprecipitates with endogenous Fas in SW480 LacZ cell lysate ( Figure 2e). As expected, this DHHC7/Fas association is enhanced when Fas WT is overexpressed (Figure 2e).…”
Section: Resultsmentioning
confidence: 81%
“…Indeed, a number of studies showed that palmitoylated proteins can assemble with their cognate DHHC during the palmitoylation process. 16,[23][24][25] We previously demonstrated that the TRAIL receptor DR4 is also palmitoylated, this palmitoylation contributing to DR4 ability to induce cell death by targeting DR4 to specific membrane nanodomains. 32 Interestingly, a recent report links DHHC3, the closest DHHC member of DHHC7, as a DR4 interacting protein by a two-hybrid screen.…”
Section: Discussionmentioning
confidence: 99%
“…Calnexin that is a major ER chaperone involved in glycoprotein folding was reported to be palmitoylated by DHHC6 with no requirement of other cofactors [68]. It seems that requirement of cofactors for PAT activity is not dependent on DHHC proteins rather it may depend on the substrates because STREX channel palmitoylation by DHHC9 [88] and calnexin palmitoylation by DHHC6 [68] do not require any cofactors for their PAT activity. More pairs of different DHHCs and their substrates are summarized in Table 2.…”
Section: Dhhc Patsubstrate Pairsmentioning
confidence: 94%
“…Further, crosstalk among these PTMs has also been demonstrated to contribute to fine tuning of the regulation of synaptic protein functions [27,260,261]. Knockdown of any DHHCs palmitoylating the alternatively spliced stress-regulated exon (STREX) variant of the intracellular C-terminal domain of the large conductance calcium-and voltage-activated potassium (BK) channels prevented the protein kinase A (PKA)-mediated inhibition of STREX channels [88], providing an evidence for an interplay between palmitoylation and phosphorylation to regulate STREX channels. In addition, a reciprocal control of synaptic targeting of PSD-95 was reported to be mediated by an interplay between palmitoylation and nitrosylation [260].…”
Section: Perspectivesmentioning
confidence: 99%
“…To identify those DHHC isoforms that are expressed in rat cardiac myocytes, we used a quantitative PCR approach similar to one that successfully determined the expression profile of DHHC isoforms in HEK cells (18). mRNA was prepared from four independent rat hearts.…”
Section: Resultsmentioning
confidence: 99%